2020
DOI: 10.1186/s12889-020-09264-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease prevention knowledge and associated factors among adults in Mukono and Buikwe districts in Uganda

Abstract: Background: With the growing epidemic of Cardiovascular Disease (CVD) in sub-Saharan Africa, behavioural change interventions are critical in supporting populations to achieve better cardiovascular health. Population knowledge regarding CVD is an important first step for any such interventions. This study examined CVD prevention knowledge and associated factors among adults in Mukono and Buikwe districts in Uganda. Methods: The study was cross-sectional in design conducted among adults aged 25 to 70 years as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Furthermore, a 2017 systematic review of 27 randomised trials found that mobile health interventions increased medication adherence, achievement of blood pressure targets, exercise, and increased awareness of diet and exercise for the secondary prevention of CVD 33 . A recent cross-sectional survey among 4,372 adults in Mukono and Buikwe districts in Uganda reported that participants who had received advice on healthy lifestyle through mobile phones had higher CVD knowledge as compared to those who had ever received healthy lifestyle advice; adjusted prevalence ratio = 1.37 (95% CI: 1.14, 1.65) 25 . However, data from recent trials of text-messaging showed null results 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a 2017 systematic review of 27 randomised trials found that mobile health interventions increased medication adherence, achievement of blood pressure targets, exercise, and increased awareness of diet and exercise for the secondary prevention of CVD 33 . A recent cross-sectional survey among 4,372 adults in Mukono and Buikwe districts in Uganda reported that participants who had received advice on healthy lifestyle through mobile phones had higher CVD knowledge as compared to those who had ever received healthy lifestyle advice; adjusted prevalence ratio = 1.37 (95% CI: 1.14, 1.65) 25 . However, data from recent trials of text-messaging showed null results 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to deal with CVD risks within the community should include sensitisation and awareness-raising to provide community members with accurate information regarding CVD and the importance of healthy lifestyle practices. Other approaches include community screening for CVD risk factors and the use of mHealth-assisted community-based CVD risk screening techniques as has been the case in Kenya [ 36 , 37 ], India [ 37 ], and Bangladesh [ 38 ]. Moreover, in the community, health workers were highlighted as a critical source of CVD information.…”
Section: Discussionmentioning
confidence: 99%
“…These improvements were achieved mostly through training, community mobilization, health education and consultation [ 38 , 40 , 45 , 46 , 49 ]. Worthy of note is that knowledge on CVD is still very low in many LMICs [ 63 , 64 ] and thus interventions are more likely to lead to significant changes. Regarding, changes in behavioral practices following implementation of intervention, greatest improvements were around physical activity with increase in proportion physically active and leisure-time activity.…”
Section: Discussionmentioning
confidence: 99%